Determination of the effect of C/N ratio on composting of vegetable-fruit wastes - Arslan Topal, E. Işil; Ünlü, Ayhan; Topal, Murat (Inderscience Publishers, 2016)
In this study, vegetable-fruit wastes were composted aerobically and the effect of various C/N ratios on the process was determined. Eight reactors with various initial C/N ratios were used. Moisture, temperature, pH, electrical conductivity (EC), C/N and cellulose were investigated during process. Moisture levels did not changed significantly by the various C/N. Among the highest temperatures reached in the reactors, the lowest ones were seen in the reactors those had the lowest C/N. The reactors with lower C/N were generally stayed at thermophilic phase shorter than the reactors which had higher C/N. The highest decrease in C/N was seen in the reactor that had an initial C/N of 25 and the lowest decrease in C/N was seen in the reactor that had the lowest initial C/N. The reactors which had higher initial C/N than the other reactors had generally lower pH values than the others. The reactor which had the lowest initial C/N had the highest pH values at the beginning of the thermophilic phase. Initial ECs in the reactors with lower C/N were higher than the others. Various C/N ratios significantly effected the cellulose contents during the process. Copyright © 2016 Inderscience Enterprises Ltd.
Keywords: C/N ratio; Composting; Fruit; Vegetable; Waste